2016
DOI: 10.1017/s0950268816000807
|View full text |Cite
|
Sign up to set email alerts
|

Unusual rotavirus genotypes in humans and animals with acute diarrhoea in Northeast India

Abstract: Rotavirus (RV) infection causes acute infantile diarrhoea in humans and animals and remains a major concern for vaccine development. The close proximity of humans to animals may foster cross-species infection resulting in the emergence of novel/unusual strains by genetic reassortment. In this study, we characterized 500 diarrhoeal samples for group A rotaviruses (RVA) from children (n = 290), piglets (n = 95) and calves (n = 115) in Northeast India during 2012-2013. The data showed that 142/500 (28·4%) faecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…Because of the segmented nature of the RV genome, novel strains can arise by reassortment during coinfection. The unusual strains are associated with 4.9% of total RV infections all over the world . Regionally, they are responsible for 14% of cases in Asia, 27% in Africa, 11% in South America, 5% in North America, 1.4% in Europe, and 0.1% in Australia …”
Section: Epidemiology Of Rvmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the segmented nature of the RV genome, novel strains can arise by reassortment during coinfection. The unusual strains are associated with 4.9% of total RV infections all over the world . Regionally, they are responsible for 14% of cases in Asia, 27% in Africa, 11% in South America, 5% in North America, 1.4% in Europe, and 0.1% in Australia …”
Section: Epidemiology Of Rvmentioning
confidence: 99%
“…The unusual strains are associated with 4.9% of total RV infections all over the world. 42,43 Regionally, they are responsible for 14% of cases in Asia, 27% in Africa, 11% in South America, 5% in North America, 1.4% in Europe, and 0.1% in Australia. 44 A rare DS-1 like G1P [8] is recently reported in Thailand, Japan, and Vietnam showing reassortment between human and animal strains.…”
Section: Novel/rare Genotypesmentioning
confidence: 99%
“…In India, circulation of mainly G6 (25-35%), G10 (50-60%) and G3 (10.2%) genotypes of bovine RV and G6 and G12 genotypes of porcine RVs have been reported (Ghosh et al, 2007;Manuja et al, 2008;Sharma et al, 2009;Ghosh et al, 2015). These findings suggest that interspecies transmission of rotaviruses between humans and animals or animals to animals might take place in nature (Nagai et al, 2015;Theuns et al, 2015;Chakraborty et al, 2016). Accordingly, animal RVAs have been considered to be of great concern for zoonotic potential and resulting in economic losses in commercial cattle farms and piggeries.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Southern India found evidence of human-to-animal transmission of a G2 RVA strain [26]. Another study in Northern India found possible reassortment between genes of animals and human RVAs resulting in circulation of unusual rotavirus genotypes [27]. …”
Section: Introductionmentioning
confidence: 99%